Answer:
a(n) = -3 - 2(n-1)
Step-by-step explanation:
The most general formula for the nth term of an arithmetic sequence (such as this sequence is) is
a(n) = a(1) + c(n-1), where c is the common difference.
Here a(1) = -3 and c = -2.
Thus,
a(n) = -3 - 2(n-1).
Answer:
Step-by-step explanation:
As the statement is ‘‘if and only if’’ we need to prove two implications
is surjective implies there exists a function
such that
.- If there exists a function
such that
, then
is surjective
Let us start by the first implication.
Our hypothesis is that the function
is surjective. From this we know that for every
there exist, at least, one
such that
.
Now, define the sets
. Notice that the set
is the pre-image of the element
. Also, from the fact that
is a function we deduce that
, and because
the sets
are no empty.
From each set
choose only one element
, and notice that
.
So, we can define the function
as
. It is no difficult to conclude that
. With this we have that
, and the prove is complete.
Now, let us prove the second implication.
We have that there exists a function
such that
.
Take an element
, then
. Now, write
and notice that
. Also, with this we have that
.
So, for every element
we have found that an element
(recall that
) such that
, which is equivalent to the fact that
is surjective. Therefore, the prove is complete.
Answer:
281 ft^2
Step-by-step explanation:
We need to add each individual 2d shape together to find the surface area
Bottom: 5*12 = 60
Left side and right side: 4*5 = 20, 2 sides so 20*2= 40
Side facing us and side facing away from us: 12*4 = 48, 2 sides so 48*2=96
Top side that is cut by base of triangle: 7*5 = 35
Each triangle face: base = 5 (12-7), height = 5 1/2base * height so each triangle is .5*5*5 = 12.5; 4 triangles so 12.5*4=50
60+40+96+35+50=281